ZnO–ZnS heterojunctions: a potential candidate for optoelectronics applications and mineralization of endocrine disruptors in direct sunlight - Perumal Devaraji; Maitri Mapa; Hasna M. Abdul Hakkeem; Vediappan Sudhakar; Kothandam Krishnamoorthy; Chinnakonda S. Gopinath (ACS Omega, 2017)
Simple solution combustion synthesis was adopted to synthesize ZnO–ZnS (ZSx) nanocomposites using zinc nitrate as an oxidant and a mixture of urea and thiourea as a fuel. A large thiourea/urea ratio leads to more ZnS in ZSx with heterojunctions between ZnS and ZnO and throughout the bulk; tunable ZnS crystallite size and textural properties are an added advantage. The amount of ZnS in ZSx can be varied by simply changing the thiourea content. Although ZnO and ZnS are wide band gap semiconductors, ZSx exhibits visible light absorption, at least up to 525 nm. This demonstrates an effective reduction of the optical band gap and substantial changes in its electronic structure. Raman spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and secondary-ion mass spectrometry results show features due to ZnO and ZnS and confirm the composite nature with heterojunctions. The above mentioned observations demonstrate the multifunctional nature of ZSx. Bare ZSx exhibits a promising sunlight-driven photocatalytic activity for complete mineralization of endocrine disruptors such as 2,4-dichlorophenol and endosulphan. ZSx also exhibits photocurrent generation at no applied bias. Dye-sensitized solar cell performance evaluation with ZSx shows up to 4% efficiency and 48% incident photon conversion efficiency. Heterojunctions observed between ZnO and ZnS nanocrystallites in high-resolution transmission electron microscopy suggest the reason for effective separation of electron–hole pairs and their utilization.